Perilaku Bullying pada Remaja Panti Asuhan Ditinjau dari Kelekatan dengan Teman Sebaya dan Harga Diri - Ritna Sandri (University of Merdeka Malang, 2015)
The purpose of this research was to identify and explains the bullying behavior among adolescent, especially in the orphanage. The research was also to investigate the effect of peer attachment and self-esteem on orphanage adolescent of bullying behavior. This research involved about 270 adolescent (13-18 years old, M=15,40 years old, S.D.=1,275) which stayed in 14 orphanages in the Malang city. The collection of data was using the instruments of the Inventory of Parent and Peer Attachment (IPPA), the Rosenberg Self-Esteem Scale (RSES) and the Adolescent Peer Relations Instrument (APRI). The results of this research show us that peer attachment and self-esteem is take effect very significant on orphanage adolescent of bullying behavior.